2013
DOI: 10.1371/journal.pone.0072890
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Differential Responses to an Oral Glucose Tolerance Test in Healthy Adults

Abstract: BackgroundIn recent years an individual’s ability to respond to an acute dietary challenge has emerged as a measure of their biological flexibility. Analysis of such responses has been proposed to be an indicator of health status. However, for this to be fully realised further work on differential responses to nutritional challenge is needed. This study examined whether metabolic phenotyping could identify differential responders to an oral glucose tolerance test (OGTT) and examined the phenotypic basis of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
87
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 76 publications
(92 citation statements)
references
References 41 publications
5
87
0
Order By: Relevance
“…The use of emerging technologies like metabolic profiling and targeted proteomics in metabolic tolerance tests has allowed the development of a new generation of biomarkers [5] by the simultaneous quantification of multiple processes [3,[6][7][8][9][10][11]. The response to challenges may be used to derive biomarkers for maintenance of physiological function and ultimately as indicator for prevention of (metabolic) diseases.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of emerging technologies like metabolic profiling and targeted proteomics in metabolic tolerance tests has allowed the development of a new generation of biomarkers [5] by the simultaneous quantification of multiple processes [3,[6][7][8][9][10][11]. The response to challenges may be used to derive biomarkers for maintenance of physiological function and ultimately as indicator for prevention of (metabolic) diseases.…”
Section: Introductionmentioning
confidence: 99%
“…The response to challenges may be used to derive biomarkers for maintenance of physiological function and ultimately as indicator for prevention of (metabolic) diseases. There is a strongly increasing interest in this type of biomarker in nutrition and health studies, demonstrating their use in uncovering early alterations in metabolism preceeding chronic diseases [9,[11][12][13][14]. Recently, it was shown that quantification of challenge response significantly contributes to demonstrating health effects of food and nutrition in dietary intervention studies [6,7,[14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Nutrients can modulate the immune response, for example particular lipids can elicit a proinflammatory state in many tissues and cell types . However, the mechanisms underlying these responses and how they relate to the metabolic phenotype remain largely unexplored . Furthermore, we do not know which biological processes respond in a different way between phenotypically distinct individuals.…”
Section: Introductionmentioning
confidence: 99%
“…Concomitant to the development of the concept of personalised dietary advice, the concept of the delivery of tailored dietary advice to a group of similar individuals has evolved , which is often referred to as targeted nutrition. Metabotyping refers to the process of grouping or stratifying individuals based on their phenotypic or metabolic profiles . It has previously been suggested that the identification of these metabotypes may pave the way forward in terms of personalised healthcare .…”
Section: Introductionmentioning
confidence: 99%